SERVICE QUALITY PANDITA LOKAPALASRAYA AND DHARMADUTA INDONESIAN BUDDHIAN ASSEMBLY - Wijoyo, Hadion; Suherman, Suherman; Khiong, Khie (EARR (Educational Administration Research and Review), 2022)
With the uneven distribution of Pandita, the guidance of the people in several places of worship is not optimal. The approach used in this study is a qualitative approach. This approach is used to examine the application of the five dimensions of service quality of Pandita Lokapalasraya and Dharmaduta MBI Pekanbaru City in 7 (seven) Viharas and Cetiya. From the results of the study, it was found that the quality of tangible services for Pandita Lokapalasraya and Dharmaduta through the indicators of the level of easy, safe and adequate parking facilities was an inhibiting factor in Pandita's service to the people. The quality of service for Pandita Lokapalasraya and Dharmaduta empathy through service demand system indicators is an inhibiting factor in Pandita's service. The quality of service responsiveness of Pandita Lokapalasraya and Dharmaduta Indonesian Buddhist Council Pekanbaru through indicators of the responsiveness level of Panditas and management of houses of worship in providing and resolving any complaints of the people, responsiveness of Panditas and management of houses of worship in serving new devotees, and responsiveness of priests and house management worship in providing information on a regular basis is an inhibiting factor in the quality of Pandita's services.